2008
DOI: 10.1113/expphysiol.2008.043174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of botulinum toxin A‐induced paralysis and exercise training on mechanosensing and signalling gene expression in juvenile rat gastrocnemius muscle

Abstract: Intramuscular injections of the paralytic botulinum neurotoxin A (Btx) and physical exercise are used in the treatment of chronic spasticity in children with cerebral palsy. We tested whether Btx-induced paralysis and/or exercise training would have differential effects on the expression of mechanosensing and signalling genes implicated in the adaptive remodelling of skeletal muscle. Juvenile (29-day-old) male rats were injected with Btx or saline (NoBtx) into the right gastrocnemius and housed in standard cag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 71 publications
2
22
0
Order By: Relevance
“…A reduction in the relative content of titin has been found in different models that induce atrophy such as hindlimb unloading, 15 hibernation, 38 and surgical denervation, 4 indicating that titin is more susceptible to degradation than the MHCs. However, in a previous study we showed that titin gene expression was upregulated in response to botulinum toxin-induced paralysis, 37 suggesting instead that the concentration of titin protein may increase in this model.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…A reduction in the relative content of titin has been found in different models that induce atrophy such as hindlimb unloading, 15 hibernation, 38 and surgical denervation, 4 indicating that titin is more susceptible to degradation than the MHCs. However, in a previous study we showed that titin gene expression was upregulated in response to botulinum toxin-induced paralysis, 37 suggesting instead that the concentration of titin protein may increase in this model.…”
mentioning
confidence: 81%
“…Thirty male Sprague-Dawley rats (including animals described in Velders et al 37 ) at 4 weeks of age were randomly allocated to five groups: (1) Baseline: sacrificed at the beginning of the study (n ϭ 6); (2) Con: received a saline injection in the right gastrocnemius muscle and housed individually in standard cages (n ϭ 6); (3) Ex: received a saline injection in the right gastrocnemius muscle and housed individually with access to a running wheel (n ϭ 6); (4) Btx: received a botulinum toxin injection (described below) in the right gastrocnemius muscle and housed individually in standard cages (n ϭ 6); and (5) Btx-Ex: received a botulinum toxin injection in the right gastrocnemius muscle and housed individually with access to a running wheel (n ϭ 6). Running distance and velocity were recorded continuously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two genes are up-regulated with a progression of muscle atrophy (Gomes et al, 2001) and the increase in mRNA expression levels of the genes is used as markers of muscle atrophy (Glass, 2005;Velders et al, 2008). We tested mRNA levels of the genes in BoNT/Ainjected gastrocnemius muscles with or without an intraperitoneal injection of ouabain.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that in some animals, BoNT/A injections made to nonspastic muscles prevented normal growth of muscle and caused progressive and persistent atrophy of muscle. In another study, it was reported that atrophy caused by BoNT/A injection was not reversed by exercise training [80,81]. There are studies reporting that injections can cause decrease in muscle strength in children with CP; nevertheless, it was reported that there was 4-5% decrease in muscle volume by injections made to gastrocnemius muscle in 15 children with CP, and this was not as dramatic as in animal experiments [73,82].…”
Section: Changes Occurring In the Intrinsic Structure Of Muscle With mentioning
confidence: 91%